Identification of Patient Characteristics Associated With SARS-CoV-2 Infection and Outcome in Kidney Transplant Patients Using Serological Screening. Issue 1 (January 2021) - Willicombe, Michelle; Gleeson, Sarah; Clarke, Candice; Dor, Frank; Prendecki, Maria; Lightstone, Liz; Lucisano, Gaetano; McAdoo, Stephen; Thomas, David
Abstract : Background: From population studies, solid organ transplant recipients are at increased risk of mortality from RT-PCR confirmed COVID-19 infection. The risk factors associated with infection acquisition and mortality in transplant recipients using serological data have not been reported. Methods: From 1725 maintenance transplant recipients, 855 consecutive patients were screened for SARS-CoV-2 antibodies. Serological screening utilized assays to detect both the N protein and receptor binding domain antibodies. Thirty-three of 855 (3.9%) of the screened patients had prior infection confirmed with RT-PCR. Twenty-one additional patients from our 1725 maintenance cohort with RT-PCR confirmed infection were included in our analysis. Results: Eighty-nine of 855 (10.4%) patients tested positive for SARS-CoV-2 antibodies. Fifty-nine of 89 (66.3%) cases were patients newly identified as exposed, while 30/89 (33.7%) seropositive patients had previous infection confirmed by RT-PCR. A diagnosis of SARS-CoV-2 (RT-PCR or Ab+) was associated with being from a noncaucasoid background, P = 0.015; having a diagnosis of diabetes, P = 0.028 and a history of allograft rejection, P < 0.01. Compared with the RT-PCR+ cohort, patients with serological-proven infection alone were more likely to be receiving tacrolimus monotherapy, P < 0.01, and less likely to have a diagnosis of diabetes, P = 0.012. Seventeen of 113 (15.0%) of all patients with infection (RT-PCR and Ab+) died. Risk factors associated with survival were older age, odds ratio (OR): 1.07 (1.00–1.13), P = 0.041; receiving prednisolone, OR: 5.98 (1.65–21.60), P < 0.01 and the absence of diabetes, OR: 0.27 (0.07–0.99), P = 0.047. Conclusions: This study identifies risk factors and outcome for COVID-19 infection incorporating data on serologically defined infection and highlights the important contribution of immunosuppression regimen on outcomes.